2014
DOI: 10.1111/ecc.12198
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for the management of cancer-related fatigue in lung cancer: a systematic review

Abstract: Cancer-related fatigue is a common, persistent and disabling side-effect of the cancer and its treatments. Exercise, once was contraindicated, is now the key non-pharmacological management for cancer-related fatigue. However, the role of exercise in lung cancer cohort is not clear. A computerised database search was undertaken using keyword search in the CENTRAL, PubMed, EMBASE, CINAHL, SPORTDiscus, AMED and Web of Science. Ten relevant articles were reviewed; the evidence on this cohort was found to be limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…While fatigue is hard to treat, physical activity and exercise may improve symptoms. 100102 In addition, targeted therapy such as angiogenesis inhibitors or drugs for LC with ALK gene mutations may also cause fatigue but it is not yet known how long fatigue symptoms may persist given the very recent use of these drugs.…”
Section: Lung Cancermentioning
confidence: 99%
“…While fatigue is hard to treat, physical activity and exercise may improve symptoms. 100102 In addition, targeted therapy such as angiogenesis inhibitors or drugs for LC with ALK gene mutations may also cause fatigue but it is not yet known how long fatigue symptoms may persist given the very recent use of these drugs.…”
Section: Lung Cancermentioning
confidence: 99%
“…More than 40 meta‐analyses or systematic reviews of RCTs have confirmed the effectiveness of physical activity/exercise to improve fatigue outcomes; with 8 of those published in the past 2 years . Study populations in which effectiveness has been demonstrated include patients with breast, colon, and prostate cancer; patients undergoing treatment with radiation, chemotherapy, or hematopoietic stem cell transplantation; young adults with cancer; and survivors who have been treated for either a solid tumor or a hematologic malignancy.…”
Section: Evidence‐based Summary Of Nonpharmacologic Interventionsmentioning
confidence: 99%
“…Exercise/physical activity has been confirmed as effective in the management of CRF in more than 40 meta-analyses or systematic reviews of randomized, controlled trials (RCTs); more than 20 of the reviews have been published since 2010 (Braam et al, 2013;Brown et al, 2011;Cramer, Lauche, Klose, Dobos, & Langhorst, 2014;Cramp & Byron-Daniel, 2012;Crandall, Maguire, Campbell, & Kearney, 2014;Eickmeyer, Gamble, Shahpar, & Do, 2012;Focht et al, 2013;Fong et al, 2012;Keogh & MacLeod, 2012;McMillan & Newhouse, 2011;Mustian, Sprod, Janelsins, Peppone, & Mohile, 2012;Paramanandam & Dunn, 2014;Payne, Wiffen, & Martin, 2012;Persoon et al, 2013;Puetz & Herring, 2012;Speck, Courneya, Mâsse, Duval, & Schmitz, 2010;Strasser, Steindorf, Wiskemann, & Ulrich, 2013;Tomlinson, Diorio, Beyene, & Sung, 2014;van Haren et al, 2013;Velthuis, Agasi-Idenburg, Aufdemkampe, & Wittink, 2010;Wolin, Ruiz, Tuchman, & Lucia, 2010;Zou, Yang, He, Sun, & Xu, 2014). Populations in which effectiveness has been demonstrated include patients with breast, colon, and prostate cancers; patients undergoing treatment with radiation, chemotherapy, or hematopoietic stem cell transplantation; young adults with cancer; and survivors who have been treated for a solid tumor or a hematologic malignancy.…”
Section: Recommended For Practicementioning
confidence: 99%
“…In their meta-analysis, Puetz and Herring (2012) noted that exercise exerts a palliative effect on fatigue during active treatment and provides a rehabilitative effect following treatment. Knowledge about the type, intensity, and duration of physical exercise most beneficial in reducing fatigue at different stages of disease and treatment is still emerging (Puetz & Herring, 2012), and more research is needed to systematically assess the safety, tolerability, and efficacy of aerobic exercise and strength training in cancer subpopulations, such as those with lung cancer (Brown et al, 2011;Paramanandam & Dunn, 2014), and across the cancer-control continuum (Wolin, Schwartz, Matthews, Courneya, & Schmitz, 2012). The exercise modalities that have been examined differ in content (walking, cycling, swimming, resistive exercise, or combined exercise), as well as frequency, duration, intensity, and degree of supervision (i.e., fully supervised groups versus self-directed exercise).…”
Section: Recommended For Practicementioning
confidence: 99%